2012
DOI: 10.3866/pku.whxb201204282
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Thermodynamics of Adsorption of Chlorophenols onto <em>&beta;</em>-Cyclodextrin Modified Chitosan

Abstract: 摘要: 制备了β-环糊精(β-CD)修饰的壳聚糖(CS)-β-环糊精-6-壳聚糖(CS-CD), 并用傅里叶变换红外(FT-IR) 光谱仪, 扫描电镜(SEM), X 射线衍射(XRD)仪和比表面分析仪(BET)进行了表征. 详细研究了其对 2-氯酚 (2-CP)、 2,4-二氯酚(DCP)和 2,4,6-三氯酚(TCP)的吸附行为和机理. 研究表明其吸附较好地满足 Langmuir 和

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…5748 2019; Yazdanpanah and Nojavan 2019). Researchers have demonstrated that modified cyclodextrin has good reusability in the absorption of organic compounds (Zhou et al 2012;Feng et al 2016). Feng et al (2016) prepared Fe3O4/hydroxypropyl-β-cyclodextrin polymer magnetic nanomaterials to absorb malachite green, and the absorption rate of the solid-phase extraction agent was 92% and could be used 5 times.…”
Section: Introductionmentioning
confidence: 99%
“…5748 2019; Yazdanpanah and Nojavan 2019). Researchers have demonstrated that modified cyclodextrin has good reusability in the absorption of organic compounds (Zhou et al 2012;Feng et al 2016). Feng et al (2016) prepared Fe3O4/hydroxypropyl-β-cyclodextrin polymer magnetic nanomaterials to absorb malachite green, and the absorption rate of the solid-phase extraction agent was 92% and could be used 5 times.…”
Section: Introductionmentioning
confidence: 99%